Intellectual outcomes of extremely preterm infants at school age. Issue 5 (21st March 2017) - Asami, Maya; Kamei, Atsushi; Nakakarumai, Misato; Shirasawa, Satoko; Akasaka, Manami; Araya, Nami; Tanifuji, Sachiko; Chida, Shoichi
Abstract: Background: The survival rate of extremely preterm (EP) infants (<28 weeks of gestation) has improved dramatically, and there is great interest in the long‐term prognosis. The aim of this study was to elucidate the influence of prenatal and postnatal care on long‐term intellectual outcome in EP infants. Methods: Subjects were EP infants admitted to the neonatal intensive care unit from 1982 to 2005. The survival rate and neurodevelopmental outcomes at 6 years of age were analyzed for the periods 1982–1991 (period 1) and 1992–2005 (period 2). Logistic regression analysis was performed to examine risk factors for intellectual impairment. Results: Survival rate improved significantly from 84.5% (period 1) to 92.4% (period 2; P = 0.007). Follow‐up data were obtained from 92 children in period 1 (69.7% of survivors) and from 245 in period 2 (72.3% of survivors). The incidence of intellectual impairment increased from 16.3% (period 1) to 31.0% (period 2). Significant factors associated with intellectual impairment were period 2 (OR, 3.53; P = 0.007), supplemental oxygen at 36 weeks' corrected age (OR, 2.22; P = 0.012), number of days in the hospital (OR, 1.01; P = 0.012), intraventricular hemorrhage (IVH; OR, 3.05; P = 0.024), and later tube‐feeding commencement date (OR, 1.10; P = 0.032). Conclusions: Despite an increase in survival rate, the rate of intellectual impairment increased in period 2. According to risk factor analysis, reducing the incidence of chronic lung disease and/or apnea, IVH, and nutritional deprivation is a key factor in improving the intellectual outcomes of EP infants.